ANALISA OVERLAY DENGAN LENDUTAN BALIK MAKSIMUM PADA JALAN Dr. MUCHTAR LUTHFI - Muhammad Shalahuddin (Jurnal APTEK, 2014)
Measurement of deflection caused by traffic loads can be connected to the pavement thicknessrequirements. Needs pavement thickness (overlay) with reverse deflection analysis tested the tool benklemanbeam. Benkleman beam test is one way to do the assessment reverse deflection pavement structure behindwhich does not damage the structure (non destructive field tests). Forth maximum vertical deflection thatoccurs on the surface of the road due to the load carried on sta eliminated. 0+000 up to 6+000 influenced bythe weather, the age of the plan, the development of traffic danAE18KSAL.